Alternative approach: a highly selective dual responding fluoride sensor having active methylene group as binding site - Das, Priyadip; Kesharwani, Manoj K.; Mandal, Amal K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Org Biomol Chem., 2012)
A newly designed phosphonium derivative (L) having active methylene functionality, shows unusual preference towards F− over all other anions. The binding process through C–H⋯F− hydrogen bond formation was probed by monitoring the changes in either electronic or luminescence spectra. Changes in both cases are significant enough to allow visual detection. The loss of molecular flexibility of L on forming L·F− effectively interrupts the non-radiative deactivation pathway and accounts for the observed switch on fluorescence response. The results of the time-resolved emission studies for L and L·F− using a time-correlated single photon counting technique further corroborate this presumption. The excellent preference of L towards F− is attributed to an efficient hydrogen bonding interaction between the strongly polarized methylene protons and F−, which delineates the subtle difference in the affinity among other competing anionic analytes like CN−, H2PO4−, CH3CO2−, etc. The relative affinities of various anions and the preferential binding of F− to reagent L are also rationalized using computational studies.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.